TINGKAT PERSEPSI MAHASISWA UNIVERSITAS LAMBUNG MANGKURAT DI KOTA BANJARMASIN TERHADAP STRATEGI PERSONAL BRANDING ROSEHAN NOOR BAHRI - Adelia Winda Hapsari (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2018)
This study aimed to find out the perception of Lambung Mangkurat University’s student to personal branding’s strategy of Rosehan Noor Bahri. The research using survey method and descriptively. Data collection using the questionnaire for respondents with a simple technique random sampling. Descriptive data analysis with quantitative. The results showed the perception of Lambung Mangkurat University’s student to personal branding’s strategy of Rosehan Noor Bahri are in the sensation level of perception.